2016
DOI: 10.1261/rna.059881.116
|View full text |Cite
|
Sign up to set email alerts
|

Will the circle be unbroken: specific mutations in the yeast Sm protein ring expose a requirement for assembly factor Brr1, a homolog of Gemin2

Abstract: A seven-subunit Sm protein ring assembles around specific U-rich RNA segments of the U1, U2, U4, and U5 snRNPs that direct pre-mRNA splicing. Using human snRNP crystal structures to guide mutagenesis in , we gained new insights into structure-function relationships of the SmD1 and SmD2 subunits. Of 18 conserved amino acids comprising their RNA-binding sites or intersubunit interfaces, only Arg88 in SmD1 and Arg97 in SmD2 were essential for growth. Tests for genetic interactions with non-Sm splicing factors ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Given the conservation from yeast to humans of the core Sm ring structure and the shared principle of RNA recognition via an amino acid triad present in each Sm subunit, one might have expected the Sm protein-RNA complex to be functionally acutely sensitive to perturbations of the protein-RNA interface and/or Sm-Sm subunit interface. This is clearly not the case in budding yeast, insofar as only two of 54 alanine mutations were lethal (Schwer and Shuman 2015;Schwer et al 2016Schwer et al , 2017. Lethal single-alanine mutations were confined to the RNA-binding sites of SmD1 (Arg88) and SmD2 (Arg97), thus highlighting the unique importance of their π-cation interactions with the sixth and seventh nucleobases of the Sm RNA site, respectively.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Given the conservation from yeast to humans of the core Sm ring structure and the shared principle of RNA recognition via an amino acid triad present in each Sm subunit, one might have expected the Sm protein-RNA complex to be functionally acutely sensitive to perturbations of the protein-RNA interface and/or Sm-Sm subunit interface. This is clearly not the case in budding yeast, insofar as only two of 54 alanine mutations were lethal (Schwer and Shuman 2015;Schwer et al 2016Schwer et al , 2017. Lethal single-alanine mutations were confined to the RNA-binding sites of SmD1 (Arg88) and SmD2 (Arg97), thus highlighting the unique importance of their π-cation interactions with the sixth and seventh nucleobases of the Sm RNA site, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…The remarkable tolerance of the seven yeast Sm proteins to mutations of the amino acids at their RNA interfaces or protein-protein interfaces suggested that the Sm ring system has built-in redundancy. To comprehensively address this issue, we conducted an "all-against-all" test of 406 different pairwise combinations of structure-guided mutations in any two of the Sm ring subunits, which unveiled a wide network of 137 intersubunit synthetic lethalities (Schwer and Shuman 2015;Schwer et al 2016Schwer et al , 2017. A key conclusion was that five of seven intact RNA-binding sites in the Sm ring do not suffice for in vivo function.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the importance of the QxDL motif was signified in the Gemin2 orthorlog protein Brr1 in S. cerevisiae by a genetic approach. The truncated BRR1-CΔ6 allele encoding Brr1(1-335), in which the last hexapeptide QKDLIE(336-341) was deleted, and the Brr1 double mutant Q336A/D338A failed to act as the wild-type Brr1 in complementing brr1Δ/SMF-F33A and brr1Δ/SME-K83A [47].…”
Section: Resultsmentioning
confidence: 99%
“…The final structure has improved quality as indicated by the reduction of R and Rfree from 25.3% and 33.2% to 21.7% and 29.5% respectively ( Supplementary Table S1). The final model (PDB code 5XJL) contains SmD1 (residues 1-81), SmD2 (residues 21-77 and 89-117), SmF (residues 3-76), SmE (residues 14-90), SmG (residues 8-52 and 55-72), Gemin2 (residues 22-31, 48-73, 79-124, 135-151, and 174-278), and SMN (residues [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Ramachandran plot shows 95.8% of the dihedral angles in favored region, 2.6% in additional allowed region, and 1.6 (9 out of 576) in disallowed region ( Supplementary Table S1).…”
Section: Re-refinement Of Crystal Structurementioning
confidence: 99%
“…Traditional genetics and synthetic genetic arraying, as well as structure-guided mutagenesis, have identified a rich network of genetically buffered functions during early spliceosome assembly in budding yeast, embracing the U1-specific snRNP proteins Mud1, Nam8, Yhc1, Snp1, and Luc7, the U1 snRNA, the TMG cap, the Cbc2•Sto1 nuclear m 7 G cap-binding complex (CBC), the DEAD-box ATPase Prp28, the Msl5•Mud2 branchpoint-binding complex, the Msl1 and Lea1 subunits of the U2 snRNP, and the seven subunits of the Sm protein ring (Liao et al 1993; Abovich et al 1994; Colot et al 1996; Gottschalk et al 1998; Staley and Guthrie 1999; Fortes et al 1999b; Chen et al 2001; Hausmann et al 2008; Wilmes et al 2008; Hage et al 2009; Costanzo et al 2010; Qiu et al 2012; 2015; Chang et al 2012; Schwer et al 2013; 2016; 2017; Schwer and Shuman 2014; 2015; Jacewicz et al 2014; 2015; Agarwal et al 2016). This network is defined by the numerous instances in which null alleles of inessential players ( e.g.…”
mentioning
confidence: 99%